1995
DOI: 10.1126/science.270.5241.1491
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Estrogen Receptor Through Phosphorylation by Mitogen-Activated Protein Kinase

Abstract: The phosphorylation of the human estrogen receptor (ER) serine residue at position 118 is required for full activity of the ER activation function 1 (AF-1). This Ser118 is phosphorylated by mitogen-activated protein kinase (MAPK) in vitro and in cells treated with epidermal growth factor (EGF) and insulin-like growth factor (IGF) in vivo. Overexpression of MAPK kinase (MAPKK) or of the guanine nucleotide binding protein Ras, both of which activate MAPK, enhanced estrogen-induced and antiestrogen (tamoxifen)-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

53
1,239
8
18

Year Published

1996
1996
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 1,807 publications
(1,318 citation statements)
references
References 34 publications
53
1,239
8
18
Order By: Relevance
“…Involvement of small GTP-binding proteins, other than Ras (Kato et al, 1995;Bunone et al, 1996), in modulation of ER activity has not been previously reported. It has been suggested that activation of a single GTPase by a Rho-GEF (such as Brx) could trigger a cascade of GTPase activation since GTP-binding proteins exist in tightly linked, but independent, regulatory circuits.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Involvement of small GTP-binding proteins, other than Ras (Kato et al, 1995;Bunone et al, 1996), in modulation of ER activity has not been previously reported. It has been suggested that activation of a single GTPase by a Rho-GEF (such as Brx) could trigger a cascade of GTPase activation since GTP-binding proteins exist in tightly linked, but independent, regulatory circuits.…”
Section: Discussionmentioning
confidence: 92%
“…This raises the possibility that Brx might indirectly a ect Rasdependent activation of the estrogen receptor. However, it does not seem that the growth factor Ras ± Raf ± MAPK pathway of ER activation is a ected by Brx, since activation of ER by the Ras ± Raf ± MAPK pathway was not inhibited by tamoxifen (Kato et al, 1995); whereas, activation of ER by Brx could be abolished by tamoxifen (Figure 5b). It is possible that cell type, or promoter-speci®c di erences might account for the di erences in response to tamoxifen, since we have not observed activation of an estrogenresponsive promter by tamoxifen in Ishikawa cells, as was observed in COS-1 cells (Kato et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations